Conspiracy theories and clinical decision-making - Stout, Nathan (Bioethics, 2023)
When a patient's treatment decisions are the product of delusion, this is often taken as a paradigmatic case of undermined decisional capacity. That is to say, when a patient refuses treatment on the basis of beliefs that in no way reflect reality, clinicians and ethicists tend to agree that their refusal is not valid. During the COVID-19 pandemic, however, we have witnessed many patients refuse potentially life-saving interventions not based on delusion but on conspiracy beliefs. Importantly, many of the beliefs espoused by conspiracy theorists resemble delusions in a number of relevant ways. For instance, conspiracy beliefs often posit states of affairs that could not possibly exist in the world, they are recalcitrant in the face of disconfirming evidence, and they tend to put the believer in a state of paranoia. Given these similarities, how should we think about conspiracy theorists' capacity for making clinical decisions? In this paper, I attempt to answer this question by first offering an account of just what makes some set of beliefs count as a conspiracy theory. Second, I attempt to disambiguate conspiracy beliefs from delusions by exploring important conceptual and psychological features of both. Finally, I apply standard criteria for assessing a patient's decision-making capacity to instances of conspiracy beliefs and argue that, although the picture is muddy, there may be cases in which conspiracy beliefs undermine capacity. I end by exploring the implications that this might have for surrogate decision-making and addressing potential objections.